2006
DOI: 10.1007/s00381-006-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

Optic pathway glioma: outcome and prognostic factors in a surgical series

Abstract: The preservation rate of ipsilateral vision was 25%, while that of contralateral vision was 83% (P<0.001). There was no remarkable endocrine improvement after surgery. The overall and progression-free survival rates at 5 years were 93.6 and 52.4%, respectively. In our study, the predictors for tumor progression were children younger than 5 years of age (p=0.023) and of female gender (p=0.022). Because of the variable course of OPG, treatment policy should be optimized individually according to patient's status. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Therefore, contemporary indications for surgery include single nerve involvement causing progressive, disfiguring proptosis, blindness, or both, or exophytic chiasm tumors causing mass effect or hydrocephalus. 2,5,54,55 Surgery is contraindicated in patients with infiltrative tumors. Although authors of numerous case reports have described spontaneous regression of OPG after surgical debulking or biopsy without additional postoperative adjuvant therapy, 25,28,54,55,84,85 it is unclear whether spontaneous regression might have occurred without any treatment at all, which has also been well-reported.…”
Section: Surgery For Opgsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, contemporary indications for surgery include single nerve involvement causing progressive, disfiguring proptosis, blindness, or both, or exophytic chiasm tumors causing mass effect or hydrocephalus. 2,5,54,55 Surgery is contraindicated in patients with infiltrative tumors. Although authors of numerous case reports have described spontaneous regression of OPG after surgical debulking or biopsy without additional postoperative adjuvant therapy, 25,28,54,55,84,85 it is unclear whether spontaneous regression might have occurred without any treatment at all, which has also been well-reported.…”
Section: Surgery For Opgsmentioning
confidence: 99%
“…Although authors of numerous case reports have described spontaneous regression of OPG after surgical debulking or biopsy without additional postoperative adjuvant therapy, 25,28,54,55,84,85 it is unclear whether spontaneous regression might have occurred without any treatment at all, which has also been well-reported. 63,66 In 2006, Ahn et al 2 retrospectively reviewed a series of 33 patients with OPGs who had undergone surgery over a 17-year period. They found that radical removal of OPGs was of no survival benefit and that it did not reduce endocrine complications.…”
Section: Surgery For Opgsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iraci et al [23] reported a series of 5 patients with precocious or pseudoprecocious puberty associated with optic nerve gliomas. Patients with suprasellar tumors have also presented with symptoms of diabetes insipidus [24], syndrome of inappropriate antidiuretic hormone hypersecretion [25], gigantism [26,27], growth hormone deficiency [28], hypothyroidism, adrenal insufficiency, and gonadotropin insufficiency [29]. Ahn et al [29] presented a series of 33 patients who underwent surgery for optic pathway gliomas; 19 had preoperative endocrine abnormalities.…”
Section: Discussionmentioning
confidence: 99%